Obstrução uretral aguda causada por tumor venéreo transmissível em um cão - Landi, Ulisses Nilo; Borges, Talita Bianchin; Quessada, Ana Maria; Borges, Jessé Lahos; de Oliveira, Dhiego Henrique; Zaniolo, Melissa Marchi; Sala, Pollyana Linhares; Ribeiro, Rita de Cássia Lima (Acta Scientiae Veterinariae, 2017)
Background: Transmissible venereal tumor (TVT) is a sexually transmitted, contagious, round cell neoplasm that affects mainly the external genital organs of dogs of both sexes. Canine TVT is practically the only tumor transmitted by cellular transplantation under natural conditions. The tumor occurs in all dog breeds and in various parts of the world, especially in the tropics and subtropics. Sexually active dogs that roam are at increased risk of acquiring the infirmity. The diagnosis is clinical, and confirmed by cytology. The most effective treatment is chemotherapy with vincristine. The aim of this report is describes a case of one male dog with an acute urethral obstruction caused by TVT. Case: In a Veterinary Medical Teaching Hospital (VMTH), a dog of unknown age was admitted. Volunteers from an animal protection institution rescued the dog from the streets after information from residents. Upon admission in the VMTH, the dog had an acute urethral obstruction, detected on clinical examination. Cystocentesis was performed to relieve the condition. Complete clinical examination and blood count were performed. Hematological examination revealed anemia and thrombocitopeny. The clinical examination revealed a swelling in the preputial area, and penile exposure was not possible. Because of this it was not possible to place the urethral catheter in the animal. However, preputial fistula and a friable, bleeding mass suggestive of a TVT were detected. For penile inspection and correction of the obstruction, the dog was submitted to a surgical procedure with an incision in the preputial midline. After the incision was made, several masses with a friable and bleeding appearance were found. The masses that prevented the urinary flow were removed and, cleansed with a physiological solution. The skin was sutured to restore the normal anatomy. In the same procedure, the dog was neutered. Cytological examination of the masses confirmed the diagnosis of TVT. After the surgery, the animal was treated with vincristine sulfate for three weeks and completely recovered. Due to the findings of the hemogram that were suggestive of hemoparasite, the animal was later referred for clinical investigation. Discussion: The animal in this case had lived on the streets, where it contracted TVT. This tumor is found most often in dogs that roam. The cystocentesis performed in the patient is used in cases of urethral obstruction in dogs where it is not possible to pass catheter. The friable and bleeding masses with ulceration that were presented by the animal, demonstrated macroscopic aspects characteristic of tumor venereal transmissible. In this type of neoplasm can appear masses in diverse places of the body, but in this dog, the masses were only in the genitalia. The urethral obstruction was caused by the masses around the urethral orifice, and urethral obstructions in dogs may be from neoplasms. The cytological examination confirmed the diagnosis, and such examination is adequate to diagnose TVT. The treatment with chemotherapy is effective to control the disease. However, in this animal, surgical intervention was necessary to restore normal urinary flow. The chemotherapy with vincristine was used after the surgical procedure to eliminate remaining masses. The animal was castrated because of the need for population control in free-living dogs. Although not common, urethral obstruction in dogs can be caused by tumor venereal transmissible.